Development of a kinetic model for Fischer-Tropsch synthesis over a Ru promoted Co/Al2O3 catalyst in a slurry reactor - Bhatelia, Tejas; Ma, W.; Jacobs, G.; Davis, B.; Bukur, D. (2011)
A detailed kinetic model for hydrocarbon formation rate over a wide range of operating conditions by using a stirred tank slurry reactor (STSR), which closely mimics the kinetics of the commercialized slurry process, is put forward. Kinetics of the Fischer-Tropsch (F-T) synthesis over 0.27% Ru 25% Co/Al 2 O 3 catalyst was studied using the STSR. Hydrogen-assisted dissociative adsorption of CO followed by hydrogenation of dissociatively adsorbed CO was the likely path for formation of the monomer (methylene) and was the likely rate controlling step in F-T synthesis. Rates obtained from the best kinetic model provided a satisfactory fit to the experimental data. This is an abstract of a paper presented at the 2011 AIChE Spring Meeting & 7th Global Congress on Process Safety (Chicago, IL 3/13-17/2011).